Análise paramétrica da vibração do solo induzida pelo tráfego ferroviário - Carvalho, Ana Flávia Paulino de (2016)
The expansion of the railway network together with the urbanization process resulted in the train induced vibrations analysis. In this work was developed a parametric analysis of ground vibration induced by railway traffic from the representation of the train through a point load, normal to the ground, moving with constant velocity. The wheel load is elastically distributed on the railway track composed by rails, sleepers and ballast, generating the resulting load on the ground. The soil is formulated as a homogeneous, elastic, isotropic and linear solid material, and their displacements are calculated by the use of triple Fourier transform, assuming that the velocity of the train traffic is less than the Rayleigh waves. The methodology of this study is based on developing a computational code using the numerical tool MATLAB. After the validation of this program, the influences of the vibrations induced by rail traffic are analyzed parametrically considering variation in the type and train speed, the characteristics of the railway track, the soil properties and the distance between the observation point and the railroad. The results show the strong influence of several parameters of the problem in the displacement and the instantaneous velocity of ground vibration, especially when the train speed approaches to the speed of Rayleigh waves in the soil. The vibration values obtained are then compared with acceptable levels of current regulations according to the type and human use of buildings which are close to the railway.